Investigation of a dynamical system in a neighborhood of an invariant toroidal manifold in the general case - Bazhura, B. P.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
A dynamical system is studied in the neighborhood of an invariant toroidal manifold for the most general relationship between the dimensionality of the phase space and the dimensionality of the manifold.